Hydrothermal synthesis of hexagonal WO3nanowires with high aspect ratio and their electrochemical properties for lithium-ion batteries - Anukorn Phuruangrat (2018)
© 2017, Pleiades Publishing, Ltd. One dimensional WO3nanowires with high aspect ratio of >200 were synthesized by hydrothermal method. The effects of reaction temperature and time on phase and morphologies were studied and discussed. In this research, a suitable hydrothermal condition is at 200°C for 48 h. XRD, SEM, and TEM results show that the product is hexagonal WO3phase with diameter of 25 nm and several ten micrometers long with growth in the c direction. The electrochemical properties were tested for rechargeable lithium batteries. The WO3NWs electrode exhibits a stability trend over the 30 cycle testing. Some long-term activation process is attributed to the WO3NWs electrode during charge/discharge reaction.